High anxiety [videorecording (Blu-Ray)] - Brooks, Mel, 1926-; Brooks, Mel, 1926-; Kahn, Madeline; Leachman, Cloris; Korman, Harvey, 1927-2008; Morris, John, 1926-2018; Lohmann, Paul (Cinematographer) (Twentieth Century Fox Home Entertainment, 2010)
After a Harvard psychiatrist takes over the Psycho-Neurotic Institute for the Very, Very Nervous, he realizes his predecessor died under suspicious circumstances and when the good doctor is accused of murder, he must faces his own great fear in order to clear his name.